The Effect of a Combination of Cacao Skin and Empty Oil Palm Fruit Bunch Fertilizer to The Growth of Basil (Ocimum Sanctum L.) - Arfika Yusti. R Harahap; Supriatno Supriatno; Hafnati Rahmatan; Muhibbuddin Muhibbuddin; Hasanuddin Hasanuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
ABSTRACT Cocoa skin and Empty Oil Palm Fruit Bunch (EOPFB) are by-products of the crop which have good nutrient content to be used as compost for basil. Basil is one of the plants used as vegetables and medicine. The purpose was to determine effect of applying cocoa skin fertilizer and EOPFB to the growth of basil and the interaction of the two fertilizers. This research is an experimental study with a quantitative approach and a factorial completely randomized design (CRD) design. The parameters of this study were plant height, number of leaves and number of basil branches. The data obtained were then analyzed using the Variance Analysis test. Based on the results of the study note that the best composition of basil growth cacao skin fertilizer is 125 g and the best EOPFB composition is 125 g. The conclusion of the research shows that the application of cocoa skin fertilizer, EOPFB and the combination of the two fertilizers have an effect on the growth of basil. Keywords: Basil, cacao skin, empty oil palm fruit bunch, fertilizer ABSTRAKKulit kakao dan Tandan Kosong Kelapa Sawit (TKKS) merupakan produk sampingan hasil panen yang memiliki kandungan hara yang baik untuk dijadikan sebagai pupuk kompos untuk kemangi. Kemangi adalah salah satu tanaman yang dijadikan lalapan dan obat. Tujuan dari riset ini untuk mengetahui apakah terdapat pengaruh dari pemberian pupuk kulit kakao dan TKKS terhadap pertumbuhan kemangi dan interaksi dari kedua pupuk tersebut. Riset ini adalah riset eksperimental dengan pendekatan kuantitatif dan desain Rancangan Acak Lengkap (RAL) faktorial. Parameter riset ini  yaitu tinggi tanaman, jumlah daun dan jumlah cabang kemangi. Data yang diperoleh kemudian dianalasis dengan menggunakan uji Analisis Varian. Berdasarkan hasil riset diketahui bahwa komposisi terbaik pupuk kulit kakao pertumbuhan kemangi adalah 125 g dan komposisi TKKS terbaik adalah 125 g. Simpulan riset menunjukkan bahwa pemberian pupuk kulit kakao, TKKS dan kombinasi dari kedua pupuk tersebut memberikan pengaruh terhadap pertumbuhan kemangi. Kata Kunci: Kemangi, kulit kakao, tandan kosong kelapa sawit, pupuk.